Impact of the Boston Active School Day Policy to Promote Physical Activity among Children. Issue 3 (January 2014) - Cradock, Angie L.; Barrett, Jessica L.; Carter, Jill; McHugh, Anne; Sproul, Jonathan; Russo, Elizabeth T.; Dao-Tran, Patricia; Gortmaker, Steven L.
Purpose: To test effectiveness of Active School Day policy implementation on physical activity outcomes and estimate school-level implementation costs. Design: The design of the study was quasi-experimental (pretest–posttest matched controls). Setting: The study took place in six elementary schools with three matched pairs in Boston, Massachusetts, February to June 2011. Subjects: Subjects were 455 consenting fourth- and fifth-grade students among 467 eligible. Intervention: Active School Day policy implementation provided equipment, curricular materials, and training to physical educators and school wellness champions to promote 150 weekly minutes of quality physical education, recess, and physical activity integrated into classrooms. Measures: Accelerometer assessments of accumulated minutes and bouts of moderate, vigorous, and sedentary physical activity on 5 school days before and after implementation were used. Implementation costs were collected by record review and reported resource utilization. Analysis: Analysis was conducted using multivariate mixed models estimated with repeated measures of daily physical activity, adjusted for student demographics and other confounding and design/clustering variables. Results: Accelerometer data were provided by 201 intervention and 192 comparison students for an average of 4 days per period (84% response). During school time, students in intervention schools demonstrated greater increases in minutes per day of moderate-to-vigorous physical activity (3.9, 95% confidence interval [CI] 1.8–6.0; p < .001) and vigorous physical activity (1.8, 95% CI.7–3.0; p < .001), and greater decreases in minutes per day of sedentary time (–10.6, 95% CI—15.3– −5.8; p < .001) than controls. Ongoing annual implementation costs totaled $4, 523/school ($14/student). Conclusion: Active School Day implementation increased student moderate-to-vigorous physical activity levels by 24% and decreased sedentary time during school at modest cost.